Penguatan Kapasitas Tata Kelola Keuangan dan Komunikasi pada Pelaksanaan Program Badan Usaha Milik Desa di Desa Gendro Pasuruan - Rachmat Kriyantono; Yun Fitrahyati Laturrakhmi; Sinta Swastikawara; Dessanti Putri Sekti Ari (Universitas Prof. Dr. Hazairin, SH, 2020)
Strengthening Financial Governance and Communication Capacity in The Implementation of Village-Owned Business Agency Programs in Gendro Village Pasuruan This article describes community service programs to provide organizational capacity strengthening to increase the Village-Owned Enterprises (BUMDES) program's effectiveness. BUMDES demands program implementers' management capabilities as a government program to develop villages, both BUMDES administrators and village governments. This management capability is related to transparency in budget management and communication management, which ultimately becomes one of the parameters that determine the level of public trust in the management of BUMDES. The Community Service Team aims to strengthen the capacity of financial governance and communication in the management of BUMDES in Gendro Village, Pasuruan Regency. Activities were carried out through workshops and assistance to BUMDES managers. This activity was attended by all BUMDES managers and village government officials. This activity was carried out from June to September 2020. This activity found that the capacity of financial and communication governance was constrained by a lack of support from the village government, communication problems between Bumdes managers and village heads, managers had not focused optimally, and low cooperation between managers. This activity was able to provide understanding and application capabilities regarding the management of transparent financial reports and effective communication management with the village government. It is hoped that this capacity will make Bumdes independent and able to innovate in developing village potentials to become a source of business for Gendro Village.